MULTIFORME EXUDATIVE ERYTHEMA AS A MANIFESTATION OF IMMUNE STRESS SYNDROME: A CLINICAL CASE - Nikolishin, Anatoliy; Kotelevska, Nataliya; Nikolishyna, Ella (Eastern Ukrainian Medical Journal, 2025)
Introduction. Immune stress syndrome, as a manifestation of autoinfectious diseases of the oral mucosa, develops under the influence of general and local factors that can affect the tolerance of the mucosa. Violation of the barrier function of the epithelium causes inflammatory autoinfectious diseases of the oral cavity. The cause of autoinfection is the disruption of local tolerance to microorganisms of normal flora and their simultaneous activation. Potential trigger factors are necessary to start the immunological reaction of the oral mucosa. These are hypothermia, prolonged dental manipulations and other stress factors. The aim of the work is to familiarize doctors with the difficulties in diagnosing and treating immune stress syndrome, which is associated with dental manipulations. Materials and methods. The article demonstrates the patient's own clinical observation and the complexity of the course of erythema multiforme exudative as a manifestation of immune stress syndrome. Results and discussion. According to the results of a general blood test, blood test for IgG and IgM to herpes virus antigens type 1, 2, bacterioscopy of scrapings from the affected areas, the diagnosis of «Stevens-Johnson syndrome with predominant damage to the oral mucosa and red border of the lips» was established and complex treatment was prescribed (detoxification, anti-inflammatory, immunotherapy). Therefore, dentists need to remember about the possibility of provoking complications after long-term dental interventions. It is imperative to conduct a clinical and laboratory examination, which allows not only to verify the diagnosis, but also to substantiate an effective treatment and prevention protocol. Conclusions. The authors of the article, to prevent the occurrence of the manifestation of «immune stress syndrome» in patients with a burdened psychosomatic status, proposed an algorithm for the doctor's actions when planning dental interventions and preventive measures that the patient should perform («Landmark for the patient»).